Percutaneous Biopsy of Hepatocellular Cancer Using Coaxial Needle System and Track Cauterization to Prevent Bleeding and Seeding. (July 2018) - Boyvat, Fatih; Haberal, Mehmet; Harman, Ali; Akdur, Aydincan; Ozyer, Umut; Selcuk, Haldun; Moray, Gokhan
Abstract : Background: Neoplastic seeding may arise after diagnostic or therapeutic percutaneous procedures for hepatocellular carcinoma (HCC). To prevent bleeding and needle track seeding of percutaneous biopsy of HCC, needle track cauterization was performed. Materials and Methods: Five patients underwent biopsy procedure. Percutaneous biopsy was performed using 17 G guiding needle and 18 G Ace-cut biopsy needle. The plastic part of 14 G intracath was used and placed to the proximal 3 cm of the guiding needle to prevent skin and subcutaneous tissue during cauterization. After several tru-cut biopsies the liver track was cauterized and the needle was removed. Median follow up is 5 months (1-8 months) Results: HCC biopsy is often mandatory for patient management by oncologists and also may give prognostic information regarding malignant potential. The incidence of needle track biopsy of liver lesions indicative of HCC is 2.7%. Numerous factors are related to the risk of neoplastic dissemination: larger diameter needles, more passes, perpendicular approach and subcapsular tumor location. Needle track seeding may lead to worsening of survival with rapid extrahepatic dissemination after liver transplantation. Conclusions: Coaxial biopsy of HCC using needle track cauterization is a new method and this preliminary study showed that it is safe and effective method.